Serotypes of Streptococcus pneumoniae causing major pneumococcal infections - Yu. V. Lobzin; S. V. Sidorenko; S. M. Kharit; S. S. Belanov; M. O. Volkova; V. V. Gostev; S. I. Aleksejenko; S. I. Petrova; E. V. Sergeeva; I. S. Koroleva; A. V. Orlov; E. Ya. Frolova (Журнал инфектологии, 2014)
First in Russia prospective non-interventional hospital-based study on Streptococcus pneumoniae serotypes causing meningitis and acute otitis media (AOM) in children and community-acquired pneumonia (CAP) in children and adults, as well as serotype coverage by pneumococcal conjugate vaccines (PCV’s) of different composition has been conducted. Serotypes 19F, 14 and serogroup 6 are the leading in meningitis; serotype coverage is 70,6% for PCV7, and 76,5% – for PCV10 and PCV13. Among S. pneumoniae serotypes causing AOM 19F, 3, 23F and serogroup 6 have been the most prevalent in Saint Petersburg. PCV7 and PCV10 provide equal serotypes coverage in AOM – 63,2% among children 0–2 years old, and 32,5% among children 5–17 years old. PCV13 covers up to 79% of serotypes in infants. In CAP PCV7 and PCV10 provide 57,1% serotype coverage in children and 56,1% – in adults. Serotype coverage in CAP for PCV13 has been 14,3% and 34,5% higher for children and adults, correspondingly. Obtained data supports PCV inclusion in children immunization program in Saint Petersburg, whereas PCV13 provides the broadest serotype coverage. In the course PCV’s implementation continued pneumococcal infection surveillance is advisable.